CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN - Jamila Abdibaeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: this article will talk about the changes and additions made to the new edition of the Constitution of the Republic of Uzbekistan, the priority directions in the general law, the importance of laws and regulations in ensuring the welfare of the people.